Pengaruh Job Insecurity, Stres Kerja dan Self Efficacy Terhadap Kinerja Karyawan PT. Bank Rakyat Indonesia kantor Cabang Bajawa - Fransiska Saferia Moi; Siti Mujanah (JURNAL RISET MANAJEMEN (JURMA), 2023)
The research was conducted with the aim of being able to analyze and determine the effect of Job Insecurity, Work Stress, Self Efficacy on Employee Performance of PT. Bank Rakyat Indonesia Bajawa Branch Office, Flores NTT. This study used a quantitative approach. Respondents for the study carried out were all employees of BRI Bajawa Branch as many as 44 r. To analyze the data, the multiple linear regression analysis method is used. The t test and F test are used in hypothesis testing. The results showed that Job Insecurity had a negative influence on employee performance Work stress did not affect employee performance and Self Efficacy had an influence on employee performance Test F results showed that Job Insecurity, Work Stress and Self Efficacy simultaneously had an influence on Employee Performance.